Environmental assessment of renewable energy conversion technologies - Fokaides, Paris A.; Morsink-Georgali, Phoebe-Zoe; Kylili, Angeliki (Amsterdam, Netherlands ; Cambridge, MA : Elsevier, 2022)
This title provides state-of-the-art coverage in both non-fossil energy conversion and storage techniques, as well as in their environmental assessment. This includes goal and scope, analysis boundaries, inventory and the impact assessment employed for the evaluation of these applications, as well as the environmental footprint of the technologies. The book compiles information currently available only in different sources concerning the environmental assessment of sustainable energy technologies, allowing for the comparative assessments of different technologies given specific boundary conditions, such as renewable potential and other specific features of discussed technologies.
Includes bibliographical references and index.
Keywords: Renewable energy sources; Energy conversion